Time-Frequency Analysis for Nonlinear Lamb Wave Signal - Hanhui Xu; Chunguang Xu; Shiyuan Zhou; Yong Hu (2009 2nd International Congress on Image and Signal Processing, 2009)
Lamb wave for ultrasonic nondestructive evaluation (UNDE) by its nonlinear effects is investigated theoretically and experimentally with time-frequency analysis. The complication of Lamb wave propagation due to its dispersive nature makes the received signal of UNDE hard to explain. Two transducers are employed in pitch-catch way together with a wedge to meet the excitation condition of low order fundamental and second harmonic lamb waves. Two time-frequency methods have been used to verify the interaction mechanism between nonlinear lamb waves with plate-like structures. The information of group velocity and out-of-plane amplitude of certain order fundamental and second harmonic lamb waves is the main means to research the nonlinear effect in this paper. The cumulative effect of second harmonic lamb wave is also researched for defect evaluation. In comparison with the results between theory and experiment, it's concluded that the pseudo Wigner-Ville distribution (PWVD) and short-time Fourier transform (STFT) are effective for processing nonlinear lamb wave signal on UNDE.